Generalized Anxiety Disorder and Treatment Options - David Scott; Emily Bebber; Kaitlynne Bizoukas; Thomas Hudgins; Michelle Scott (Academia Edu Cendekia Indonesia (AEDUCIA), 2026)
Background: Generalised Anxiety Disorder (GAD) is a chronic mental health condition characterised by persistent and excessive worry that lasts for at least six months and interferes with daily functioning. The disorder affects adolescents and adults worldwide and is frequently accompanied by psychological and somatic symptoms such as restlessness, fatigue, sleep disturbance, irritability, and impaired concentration. Because these symptoms often appear in primary health settings, accurate diagnosis remains challenging. Objective: This article reviews the aetiology, clinical characteristics, and current treatment options for GAD, highlighting emerging therapeutic approaches. Method: The study employs a narrative literature review of recent psychological and psychiatric publications on diagnostic criteria, epidemiology, pharmacological management, and cognitive-behavioural interventions. Results: Findings indicate that GAD presents with diverse symptom trajectories across the lifespan and disproportionately affects certain populations, including women and older adults. Evidence also shows that combined pharmacotherapy and cognitive behavioural therapy remains the most effective treatment, while mindfulness-based and integrative therapies demonstrate promising complementary outcomes. Conclusion: Comprehensive and individualised treatment is essential for improving long-term symptom management and quality of life. Contribution: This review synthesizes evidence supporting clinical practice.